An analysis of pregnancy-related mortality in the KEMRI/CDC health and demographic surveillance system in western Kenya. - Meghna Desai; Penelope A Phillips-Howard; Frank O Odhiambo; Abraham Katana; Peter Ouma; Mary J Hamel; Jackton Omoto; Sheila Macharia; Annemieke van Eijk; Sheila Ogwang; Laurence Slutsker; Kayla F Laserson (PLoS ONE)
Background Pregnancy-related (PR) deaths are often a result of direct obstetric complications occurring at childbirth. Methods and findings To estimate the burden of and characterize risk factors for PR mortality, we evaluated deaths that occurred between 2003 and 2008 among women of childbearing age (15 to 49 years) using Health and Demographic Surveillance System data in rural western Kenya. WHO ICD definition of PR mortality was used: "the death of a woman while pregnant or within 42 days of termination of pregnancy, irrespective of the cause of death". In addition, symptoms and events at the time of death were examined using the WHO verbal autopsy methodology. Deaths were categorized as either (i) directly PR: main cause of death was ascribed as obstetric, or (ii) indirectly PR: main cause of death was non-obstetric. Of 3,223 deaths in women 15 to 49 years, 249 (7.7%) were PR. One-third (34%) of these were due to direct obstetric causes, predominantly postpartum hemorrhage, abortion complications and puerperal sepsis. Two-thirds were indirect; three-quarters were attributable to human immunodeficiency virus (HIV/AIDS), malaria and tuberculosis. Significantly more women who died in lower socio-economic groups sought care from traditional birth attendants (p = 0.034), while less impoverished women were more likely to seek hospital care (p = 0.001). The PR mortality ratio over the six years was 740 (95% CI 651-838) per 100,000 live births, with no evidence of reduction over time (χ(2) linear trend = 1.07; p = 0.3). Conclusions These data supplement current scanty information on the relationship between infectious diseases and poor maternal outcomes in Africa. They indicate low uptake of maternal health interventions in women dying during pregnancy and postpartum, suggesting improved access to and increased uptake of skilled obstetric care, as well as preventive measures against HIV/AIDS, malaria and tuberculosis among all women of childbearing age may help to reduce pregnancy-related mortality.